Optimization Of Wear Behaviour Of LM26-Gr Composite Using Taguchi Based Grey Relational Analysis - et. al., K. Lakshmi Chaitanya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The progression in present manufacturing technology created the need of developing new materials for superior wear resistance. The objective of this paper is to optimize the three process parameters wear loss, wear rate, specific wear at three different levels with Taguchi technique in L9 Orthogonal array. A multi-response optimization technique Grey relational analysis is used to obtain the single process parameter setting for both the responses. LM26 metal matrix composite is fabricated by stir casting technique with Almandine garnet particles as reinforcement in different weight percentages with two different particle sizes. Analysis of Variance (ANOVA) was conducted to recognize the prevalent factor and found all the three factors as being critical. The above process was validated by Linear regression technique after conformation tests has been performed.